Size-dependent regulation of soil microbial functional-network structure by polystyrene microplastics - Guanlin Li; Junliang Chen; Yi Tang; Xiaoxun Zhao; Sushu Cui; Babar Iqbal; Pengfei Cheng; Tingting Zhao; Daolin Du; Peng Wang (Applied Soil Ecology, 2026)

Compartmental pH regulation in cancer and antitumor immunity: therapeutic opportunities and challenges - Fangquan Chen; Xiutao Cai; Qile Zhou; Zhen Huang; Jie Wang; Rui Kang; Daolin Tang; Jiao Liu (Apoptosis, 2026)

Photothermal-brick for on-site zero liquid discharge treatment of high-salinity wastewater - Xuxiao Luo; Yingru Li; Xin Yang; Daolin Quan; Yulin Ran; Youshuai Lan; Jianfeng Zhang; Yahui Yang; Jinyu Liu; Zihao Luo; Zhuxin Jiang; Miaowei Zhang; et al. (Environmental Research, 2026)

Role of biochar in reducing polyethylene and polylactic acid microplastic co-contamination with antibiotics in soil-vegetable systems - Pengfei Cheng; Junliang Chen; Muhammad Tariq; Lei Tang; Zebin Hong; Babar Iqbal; Ismail Khan; Guanlin Li; Daolin Du; Tongxu Liu (Process Safety and Environmental Protection, 2025)

Critical Threshold of Microbial Carbon Use Efficiency Regulates Soil Carbon Dynamics Under Solidago canadensis Invasion - Abdulkareem Raheem; Yijin He; Guanlin Li; Babar Iqbal; Qiuyue Zhang; Yi Tang; Sixuan Xu; Hyun-Jun Kim; Zhicong Dai; Jian Li; Xiaojun Zheng; Daolin Du (Journal of Soil Science and Plant Nutrition, 2025)

Concurrent alien plant invasion and biodiversity loss enhance soil microbial carbon use efficiency by shifting the balance between microbial carbon and nitrogen acquisition - Abdulkareem Raheem; Babar Iqbal; Yanjiao Wang; Jiabao Lou; Yi Tang; Jian Li; Qiuyue Zhang; Sixuan Xu; Zhicong Dai; Xiaojun Zheng; Guangqian Ren; Guanlin Li; et al. (Journal of Environmental Management, 2025)

Spartina alterniflora invasion altered soil greenhouse gas emissions via affecting labile organic carbon in a coastal wetland - Guanlin Li; Sixuan Xu; Yi Tang; Yanjiao Wang; Jiabao Lou; Qiuyue Zhang; Xiaojun Zheng; Jian Li; Babar Iqbal; Pengfei Cheng; Aibin Zhan; Daolin Du (Applied Soil Ecology, 2024)

The promoting effects of soil microplastics on alien plant invasion depend on microplastic shape and concentration - Guanlin Li; Yi Tang; Jiabao Lou; Yanjiao Wang; Shiyu Yin; Lianghui Li; Babar Iqbal; Yudi M. Lozano; Tingting Zhao; Daolin Du (Science of The Total Environment, 2024)

Effects of degradable and non-degradable microplastics and oxytetracycline co-exposure on soil N2O and CO2 emissions - Kiran Yasmin Khan; Yi Tang; Pengfei Cheng; Yunliang Song; Xinyu Li; Jiabao Lou; Babar Iqbal; Xin Zhao; Rashida Hameed; Guanlin Li; Daolin Du (Applied Soil Ecology, 2024)

Unraveling the ecological threads: How invasive alien plants influence soil carbon dynamics - Abdulkareem Raheem; Paul Yohanna; Guanlin Li; Nam Jin Noh; Babar Iqbal; Jing Tang; Daolin Du; Tahani Awad Alahmadi; Mohammad Javed Ansari; Aibin Zhan; Yowhan Son (Journal of Environmental Management, 2024)

ATF4 in cellular stress, ferroptosis, and cancer - Hu Tang; Rui Kang; Jiao Liu; Daolin Tang (Archives of Toxicology, 2024)

Duloxetine-Induced Neural Cell Death and Promoted Neurite Outgrowth in N2a Cells - Wanli Gao; Rui Chen; Nan Xie; Daolin Tang; Borong Zhou; Ding Wang (Neurotoxicity Research, 2020)
Duloxetine is a clinical drug that is primarily used for treatment of depression and pain, but it has side effects of addiction and tolerance. Cytochrome P450 (CYP) is its metabolic enzyme, and the drug’s biofunction results from its neuro-protective effect in animal and cell models. We aimed to investigate the duloxetine-induced neural cytotoxicity effect and its performance in an N2a cell neurite outgrowth model. Cell death was assessed as cell viability using a Cell Count Kit-8 and further evaluated using bright-field images, propidium iodide (PI) and annexin V staining, colony-formation analysis, TUNEL staining of the cells, and biochemical testing. N2a cells were committed to differentiation by serum withdrawal and RA induction, and the neurite outgrowth was evaluated as the number of differentiated cells, longest neurite length, and average neurite length. Cell cycle analysis, PI and annexin V staining, mRNA expression, and biochemical testing were used to evaluate the drug effects on differentiation. The induction of neural cell death by duloxetine was not affected by classic cell death inhibitors but was promoted by the CYP inducer rifampicin. N2a cell neurite outgrowth was promoted by duloxetine via reduction of the CYP2D6 and MDA levels and induction of Bdnf protein levels. Duloxetine induces neural cell death through effects on CYP and promotes N2a cell neurite outgrowth by regulating CYP, Bdnf protein, and the intracellular lipid peroxidation level.

Metal-based proteasomal deubiquitinase inhibitors as potential anticancer agents - Xin Chen; Qianqian Yang; Lu Xiao; Daolin Tang; Q. Ping Dou; Jinbao Liu (Cancer and Metastasis Reviews, 2017)